(untitled) (Czech Journal of International Relations, 1967)
Among the questions that are often the subject of international ones recently conferences, especially the issue of economic relations between East and West. Individual aspects from the whole complex of the problems of this kind, however, are also dealt with in practice with an intensity that no one would have expected, which concerns both socialist countries and the majority of advanced capitalist countries. My experience so far indicates that it is not a matter of moments, frankly transient phenomenon; the matter has, in particular, a deeper and more binding meaning. It follows especially from the analysis of the specific conditions of the economic development process contact between East and West.